Experimental study on the effect of air throttling on supersonic combustion. (March 2018) - Tian, Ye; Yang, Shunhua; Xiao, Baoguo; Le, Jialing
The effect of air throttling on supersonic combustion was investigated by experiments in the present paper. Our results indicated that, in the non-reacting flow, a shock train could be generated in the scramjet combustor due to the increased backpressure caused by air throttling, and the wall pressure increased obviously. But when the mass flux rate of air throttling was not large enough, the shock train would oscillate with the flow. In the reacting flow, the flame stabilization was achieved in the combustor without air throttling when the equivalence ratio of kerosene was 0.2 and 0.31, but the flame was blown off when the equivalence ratio of kerosene was 0.45. On the contrary, the kerosene (equivalence ratio: 0.45) was ignited successfully in the combustor with air throttling, and it kept burning all the time in the cases with air throttling −5% (the flux of air throttling was 5% of the inflow flux) and with air throttling −14% (the flux of air throttling was 14% of the inflow flux), but the flame was blown off in the case with air throttling −1.1% after kerosene had burnt 70 ms. The flux of air throttling should be large enough to achieve flame stabilization, and the hydrogen and air throttling should both exist all the time in order to keep the flame burning steadily.